Emotional control and factors differentiating it in the adult population of Poland during the COVID-19 pandemic - Głogowska-Gruszka, Anna; Wypych-Ślusarska, Agata (Frontiers in Psychology, 2023)
The public health crisis related to the COVID-19 pandemic has had a negative impact on the mental health of both individuals and entire populations. The source of stress was not only the fear of getting sick, but also the restrictions introduced, such as: mass lockdown, the need to maintain social distance, quarantine or the mandatory use of personal protective equipment. Their introduction and maintenance caused various emotional reactions which often resulted in undesirable behavior leading to infections spreading. The aim of the study was to analyse the level of emotional control depending on selected factors related to the pandemic and the introduced restrictions. The study covered 594 adult Poles. To evaluate knowledge about COVID-19 and attitudes towards the implemented restrictions, the questionnaire prepared by the authors was used. To determine the level of control of anger, depression and anxiety the Courtauld Emotional Control Scale (CECS) was used, and to estimate the level of perceived stress the Perceived Stress Scale (PSS-10) was applied.In the entire analyzed group, the general level of emotional control was 51.82±12.26, with anxiety being the most suppressed emotion (17.95±4.99), whereas the least suppressed emotion was anger (16.35±5.15). The average stress level in the studied group was 20.5±5.3. The level of perceived stress did not differentiate the level of emotional control. It was found that the higher level of the knowledge about the pandemic and methods of prevention, the higher emotional control, especially in the anxiety subscale (high level of knowledge - 18.26±5.36 vs. low level of knowledge - 15.09±3.6; p= 0.02). People reporting difficulties in reconciling remote work with home duties were less able to control anger (14.63±4.98) than people without such problems (16.71±4.12; p=0.007). Proper education improving knowledge about COVID-19 and methods of prevention may enhance the control of emotions in the population. Possible future preventive measures aimed at limiting the spread of SARS-CoV-2 infections or other infectious diseases should also take into account possible excessive mental burden caused by private and professional duties.